2023
DOI: 10.1007/s10008-023-05443-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry needs electrochemists: “goodbye to rotating discs”

Abstract: The essential need for expert, fully trained electrochemists in the successful application of the subject is illustrated with several examples including the use of rotating electrodes and impedance spectroscopy where the use of the techniques in “black box” mode non-experts is likely to lead to disappointment or embarrassment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…With the modification of the different molecules at the GCE interface, the impedance of the GCE increased gradually (TPE-2SO 3 Na > TPE-4SO 3 Na > C 4 H 8 -2SO 3 Na > Bare GCE). The increasing impedance indicated that the electrode interface coverage increased gradually, which further indicated that π-conjugated molecules were increasingly modified on the electrode. , It was confirmed that the gradual increase of the GCE interface of the π-conjugated structure could promote the π–π interaction with Ru­(bpy) 3 2+ , resulting in signal amplification, which was consistent with the ECL signal enhancement trend shown in Figure A. To further study the effect of the π–π interaction on the Ru­(bpy) 3 2+ -TPA ECL system, CV curves were measured on the bare GCE and the sulfonic acid-functionalized molecule-modified electrode (Figure S19).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…With the modification of the different molecules at the GCE interface, the impedance of the GCE increased gradually (TPE-2SO 3 Na > TPE-4SO 3 Na > C 4 H 8 -2SO 3 Na > Bare GCE). The increasing impedance indicated that the electrode interface coverage increased gradually, which further indicated that π-conjugated molecules were increasingly modified on the electrode. , It was confirmed that the gradual increase of the GCE interface of the π-conjugated structure could promote the π–π interaction with Ru­(bpy) 3 2+ , resulting in signal amplification, which was consistent with the ECL signal enhancement trend shown in Figure A. To further study the effect of the π–π interaction on the Ru­(bpy) 3 2+ -TPA ECL system, CV curves were measured on the bare GCE and the sulfonic acid-functionalized molecule-modified electrode (Figure S19).…”
Section: Resultssupporting
confidence: 67%
“…The increasing impedance indicated that the electrode interface coverage increased gradually, which further indicated that π-conjugated molecules were increasingly modified on the electrode. 36,37 It was confirmed that the gradual increase of the GCE interface of the π-conjugated structure could promote the π−π interaction with Ru(bpy) 3…”
Section: +mentioning
confidence: 92%
“…The desire to extract more information from the RDE and RRDE measurements than possible leads to the misuse of these techniques . The models are based on flat and smooth electrodes, meaning the macroscopically rough (nonflat and nonuniform) catalyst layers can cause additional complications.…”
Section: Comparison Of Methods: Critical Differencesmentioning
confidence: 99%
“…The rotating disk electrode is the most popular hydrodynamic electrode and is widely used by electro-analysts as well as fundamental electrochemists, not least since the device provides a well-defined convective flow of solution (analyte) to the electrode surface, allowing steady-state measurements. 12 A schematic flow profile is shown in Figure 1 a,b and the resulting diffusion-controlled currents have long been known, arising from the theoretical work of Levich 13 and rigorously validated experimentally by the Frumkin School of Electrochemistry. 14 In particular, Levich established the following equation for the transport-controlled steady-state current and diffusion layer thickness at the rotating electrode where the symbols are defined in Table 1 .…”
Section: Introductionmentioning
confidence: 99%